2021
DOI: 10.1002/ecs2.3691
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate scavenging dynamics differ between carnivore and herbivore carcasses in the northern boreal forest

Abstract: Vertebrate scavenging can impact food web dynamics, but our understanding of this process stems predominantly from monitoring herbivore carrion and extrapolating results across carcass types. Recent evidence suggests carnivores may avoid intraguild scavenging to reduce parasite transmission. If this behavior is widespread across diverse ecosystems, estimation of nutrient cycling and community scavenging rates are likely biased to a currently unknown degree. We examined whether the time to initiate scavenging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…We distinctly tested assumptions regarding carrion avoidance behaviors and scavenger sensory recognition mechanisms in our study using a robust sample size of a common North American carnivore species. Our findings further support carcass types from different trophic levels are used differently by vertebrate scavengers, and that mammalian carnivore carrion is avoided broadly by other mammal carnivores 12 , 18 , 28 . The longer persistence times of carnivore carrion likely plays a role in the transfer of higher trophic level carrion nutrients into soil microbial, plant, and invertebrate communities 17 , 35 , 56 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We distinctly tested assumptions regarding carrion avoidance behaviors and scavenger sensory recognition mechanisms in our study using a robust sample size of a common North American carnivore species. Our findings further support carcass types from different trophic levels are used differently by vertebrate scavengers, and that mammalian carnivore carrion is avoided broadly by other mammal carnivores 12 , 18 , 28 . The longer persistence times of carnivore carrion likely plays a role in the transfer of higher trophic level carrion nutrients into soil microbial, plant, and invertebrate communities 17 , 35 , 56 .…”
Section: Discussionsupporting
confidence: 78%
“…Several scavenging studies have used carcasses that were not fully intact including partially or fully skinned, eviscerated, and/or head and feet removed 18 , 27 , 28 . Yet, few of these assessed how these alterations, and thus external characteristics and associated chemical stimuli, influence scavengers’ feeding decisions (but see Moleón et al 12 and Selva et al 29 ), and most had limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that carnivore carcasses persisted longer and showed lower consumption rates than herbivore carcasses (Oliva‐Vidal et al 2021, Peers et al 2021). However, contrary to our predictions, we detected no differences in species richness, abundance and detection time between herbivore and carnivore carcasses.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have shown that mammalian carnivores tend to avoid scavenging fresh carcasses from conspecifics or closely related species, which is likely to reduce the risk of parasitic infection (Gonzálvez et al., 2021). In the boreal forests of Canada, even in winter when prey is scarce, it took longer for vertebrate scavengers to initiate scavenging of carnivore carcasses than herbivore carcasses and carnivore carcasses persisted in the landscape for longer periods than herbivore carcasses (Peers et al., 2021). At our study site, brown bears and Japanese martens visited raccoon carcasses but never scavenged them in the summer (Table S2).…”
Section: Discussionmentioning
confidence: 99%